Evaluation Of Takagi-Sugeno Fuzzy Inference for Estimating Evapotranspiration In Mila-Algeria's Sub-Humid Climate - Meziani Assia; Miloudi Abdelmonen; Lembarek Mohammed Sayah (University Of Ghardaia, 2024)
Effective water resource management is crucial for sustaining agricultural productivity, particularly in regions prone to water scarcity. The FAO-56 method, developed by the Food and Agriculture Organization, has become a cornerstone for accurately estimating reference evapotranspiration (ET₀), a key component in understanding water requirements for crops. The FAO-56 method integrates key meteorological data—temperature, humidity, wind speed, solar radiation, and other climatic parameters to provide accurate and consistent ET estimates, which are crucial for effective water resource management in agriculture. To enhance ET estimation in the sub-humid region of Mila, Algeria, a Takagi-Sugeno (TS) fuzzy inference system model was developed. The TSFS model demonstrated strong performance with low RMSE (0.417-0.434), high R² (0.945-0.950), and a high Willmott index (0.827-0.831), indicating reliable and accurate ET predictions for the Mila region. These results suggest that the Takagi-Sugeno fuzzy inference system is a viable alternative to traditional methods, offering robust ET estimates tailored to the specific climatic conditions of Mila, Algeria. الملخص: إدارة موارد المياه بشكل فعّال أمر حاسم للحفاظ على إنتاجية الزراعة، خاصة في المناطق المعرضة لنقص المياه. أصبحت طريقة FAO-56، التي طورتها منظمة الأغذية والزراعة، لتقدير التبخر والنتح المرجعي (ET₀) بدقة، وهو عنصر رئيسي لفهم احتياجات المياه للمحاصيل. تدمج طريقة FAO-56 بيانات الأرصاد الجوية الرئيسية - مثل درجة الحرارة، والرطوبة، وسرعة الرياح، والإشعاع الشمسي، وغيرها من المعايير المناخية - لتقديم تقديرات دقيقة ومتسقة للتبخر والنتح المرجعي ـ ET، والتي تعتبر اساسية لإدارة موارد المياه بشكل فعّال في الزراعة. لتعزيز تقدير ET في المنطقة شبه الرطبة في ميلة، الجزائر، تم تطوير نموذج نظام استدلال ضبابي من نوع تاكاغي-سوجينو (TS). أظهر نموذج TSFS أداءً قويًا مع خطأ جذر متوسط مربع منخفض (0.417-0.434)، وقيمة R² عالية (0.945-0.950)، ومؤشر ويلموت مرتفع (0.827-0.831)، مما يشير إلى توقعات ET فعالة ودقيقة لمنطقة ميلة. تشير هذه النتائج إلى أن نظام الاستدلال الضبابي لتاكاغي-سوجينو هو بديل قابل للتطبيق للطرق التقليدية، حيث يقدم تقديرات ET جيدة تتناسب مع الظروف المناخية الخاصة بميلة، الجزائر.
Intervention
Keywords: Evapotranspiration; FAO-56; Takagi-Sugeno Fuzzy System; Model; Sub-humid; Mila; Algeria; التبخر والنتح; طريقة; FAO-56; نظام تاكاغي; سوجينو الضبابي; نموذج; شبه رطب; ميلة; الجزائر